DIFFERENTIAL SANDWICH THEOREMS FOR SOME SUBCLASS OF ANALYTIC FUNCTIONS ASSOCIATED WITH LINEAR OPERATORS - T.N. Shanmuguam; M.P. Jeyaraman; A. Singaravelu (Journal of the Indonesian Mathematical Society, 2007)
" PDF file" DOI : http://dx.doi.org/10.22342/jims.13.1.73.39-50